MODERN PREVENTIVE STRATEGIES FOR DENTAL CARIES IN PERMANENT TEETH OF CHILDREN WITH DIABETES MELLITUS: A THEORETICAL AND EVIDENCE-BASED ANALYSIS (International journal of medical sciences, 2026)
Dental caries remains one of the most prevalent chronic diseases in childhood, and its burden is significantly amplified in children diagnosed with diabetes mellitus. Persistent hyperglycemia, altered salivary composition, immune dysregulation, and increased oral microbial pathogenicity collectively contribute to a higher caries risk in permanent dentition. The present article provides a comprehensive theoretical and evidence-based analysis of contemporary preventive strategies for dental caries in children with diabetes. Epidemiological data indicate that the global prevalence of diabetes among children and adolescents is steadily increasing, while caries prevalence in this group ranges from 40% to 75% depending on glycemic control and socioeconomic conditions. Modern preventive approaches extend beyond traditional fluoride application and encompass individualized risk assessment, metabolic stabilization, minimally invasive dentistry, antimicrobial modulation, salivary diagnostics, dietary counseling, digital monitoring technologies, and interdisciplinary care models. Scientific literature demonstrates that well-controlled glycemic status significantly reduces caries incidence and improves salivary flow and buffering capacity. Preventive protocols integrating professional fluoride varnish, pit and fissure sealants, bioactive remineralizing agents, and structured recall systems have shown measurable reductions in DMFT indices. The article synthesizes findings from clinical studies, systematic reviews, and theoretical models to propose an integrated prevention framework. Emphasis is placed on personalized, evidence-based, and metabolically oriented caries prevention strategies tailored specifically for children with diabetes mellitus.